The long history of financial boom-bust cycles in Iceland - Part I: Financial crises - Bjarni G. Einarsson; Kristófer Gunnlaugsson; Thorvardur Tjörvi Ólafsson; Thórarinn G. Pétursson
Iceland suffered a severe financial crisis in 2008 which can only be described as the perfect storm, with the currency falling by more than 50% and over 90% of the domestic financial system collapsing. What followed was a deep recession. This was not the first financial crisis experienced in Iceland, however. In fact, over a period spanning almost one and a half century (1875-2013), we identify over twenty instances of financial crises of different types. Recognising that crises tend to come in clusters, we identify six serious multiple financial crisis episodes occurring every fifteen years on average. These episodes seem to share many commonalities and the tragic but universal truth that “we’ve been there before” when it comes to financial crises really becomes all too clear. We find that these episodes usually involve a large collapse in domestic demand that in most cases serves as a trigger for theensuing crisis. What typically follows is a currency crisis, sometimes coinciding with a sudden stop of capital inflows and an inflation crisis, and most often a banking crisis. In line with international evidence, we find that contractions coinciding with these large financial crises tend to be both deeper and longer than regular business cycle downturns. Although the crisis episodes share many common elements, each one of them is also different to some extent. We are therefore not able to find financial variables that consistently provide an early-warning signal of an upcoming financial crisis across all the six episodes. However, we find that some key macroeconomic variables give a somewhat more robust signal. Our results also suggest that five of the six multiple crisis episodes coincide with a global financial crisis of some type, and that the most serious global episodes coincide with a twoto threefold increase in the probability of a financial crisis in Iceland. A companion paper (Part II) extends our analysis of the Icelandic financial boom-bust cycle to identifying financial cycles in our long data set, ...